Mesenchymal stem cells: A novel treatment option for primary sclerosing cholangitis. (2nd November 2022) - Lightner, Amy L.; Dadgar, Neda; Vaidya, Anil; Simon, Robert; Fulmer, Clifton; Siddiki, Hassan; Narayanan Menon, K. V.; Liu, Peter; Matthew Walsh, R.
Abstract: Primary sclerosing cholangitis (PSC) is a progressive liver disease for which there is no effective therapy. Hepatocytes and cholangiocytes from a PSC patient were cocultured with mesenchymal stem cells (MSCs) to assess in vitro change. A single patient with progressive PSC was treated with 150 million MSCs via direct injection into the common bile duct. Coculture of MSCs with cholangiocytes and hepatocytes showed in vitro improvement. Local delivery of MSCs into a single patient with progressive PSC was safe. Radiographic and endoscopic evaluation showed stable distribution of multifocal structuring in the early postoperative period. MSCs may be effective for the treatment of PSC.